Oil product tanker geography with emphasis on the Handysize segment - Risto Laulajainen (Fennia: International Journal of Geography, 2011)
Novel movement data are used to chart worldwide mineral oil product shipments by Handysize (15,000–59,999 dwt) and larger (60,000+ dwt) tankers. The data are from 2004 which allows comparisons with earlier studies about crude oil shipments. Theory about ship movements and attached freight rates (RP Rule) gets indirect support. Non-existence of global data below the Handysize enforces the use of fragmentary data from a refinery company and a world-class port. Both data sets are believed to be representative for the purposes used. Exportshipments of the refinery company reveal a linear non-logarithmic distance function for vessel classes in the 2,000–67,000 dwt range. The function is practically identical with oil product exports from the said port. The thinking is then extended to larger vessel sizes and crude oil cargoes, the principle of fungibility.